2019
DOI: 10.1627/jpi.62.220
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Noble-metal Nanoparticles by Microwave-assisted Chemical Reduction and Evaluation as Catalysts for Nitrile Hydrogenation under Ambient Conditions

Abstract: Herein, we report a protocol for rapid preparation of uniformly sized Ru, Rh, Pd, Ir, and Pt nanoparticles stabilized by poly(N-vinyl-2-pyrrolidone) via microwave-assisted chemical reduction with ethanol. Although the boiling point of ethanol, which has high reduction ability, is much lower than the temperature required for metal cation reduction, this solvent could be used as a reductant because the preparation was carried out in a sealed vessel. All metal nanoparticles showed similar sizes and amounts of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In addition, a Rh catalyst with a Rh particle size of 2.7 nm showed high activity in the hydrogenation of benzonitrile to a secondary imine and showed reusability in the hydrogenation of nitriles (30 • C, 3 bar H 2 ) [45]. Ru, Rh, Pd, Ir, and Pt nanoparticles stabilized by poly(N-vinyl-2-pyrrolidone) (PVP) with a uniform size were prepared by chemical reduction with ethanol in the microwave oven [46]. All metallic nanoparticles had a similar size and the same amount of PVP.…”
Section: Synthesis Of Catalysts Using Microwave Radiationmentioning
confidence: 99%
“…In addition, a Rh catalyst with a Rh particle size of 2.7 nm showed high activity in the hydrogenation of benzonitrile to a secondary imine and showed reusability in the hydrogenation of nitriles (30 • C, 3 bar H 2 ) [45]. Ru, Rh, Pd, Ir, and Pt nanoparticles stabilized by poly(N-vinyl-2-pyrrolidone) (PVP) with a uniform size were prepared by chemical reduction with ethanol in the microwave oven [46]. All metallic nanoparticles had a similar size and the same amount of PVP.…”
Section: Synthesis Of Catalysts Using Microwave Radiationmentioning
confidence: 99%
“…STEM-EDXS maps of the resulting nanoparticles showed that the Pd-L and Pt-L signals were localized at the interior and exterior of the particles, respectively (Figure S11b-f), which indicates the formation of a Pd-rich core and a Pt-rich surface phase. Furthermore, the small particles produced by heterogeneous heating from the mantle heater 34 were composed mainly of Pt species. On the basis of these experimental results, we propose that the alloying mechanism involves rapid and simultaneous reduction of the readily reducible [PdCl 4 ] 2− and [PtCl 4 ] 2− ions by microwave heating.…”
Section: Dependence Of Catalytic Performance On Metal Composition Of ...mentioning
confidence: 99%
“…Recently, we demonstrated for the first time that Rh nanoparticles stabilized by PVP effectively catalyze the selective formation of secondary imines from nitriles by hydrogenation under ambient conditions (25 °C and 1 bar). 33,34 Herein, we report an effective method for nitrile hydrogenation that affords secondary amines under ambient conditions over newly developed PdPt-PVP nanoparticle catalysts. Random alloying by chemical reduction generated PdPt-PVP nanoparticles, despite the fact that Pd and Pt are classically immiscible below 700 °C.…”
Section: Introductionmentioning
confidence: 99%